Photosynthetic Performances of Marine Microalgae Under Influences of Rising CO2 and Solar UV Radiation - Gao, Kunshan; Häder, Donat-Peter (Springer Singapore, 2020)
Marine photosynthesis contributes approximately half of the global primary productivity. Ocean climate changes, such as increasing dissolved CO2 in seawater and consequently declining pH (known as ocean acidification, OA), may alter marine photosynthetic performance. There are numerous studies on the effects of OA on photosynthetic organisms, but controversial findings indicate positive, neutral, and negative influences. Most of the studies so far have been conducted under controlled conditions that ignored the presence of solar UV radiation. Increased CO2 availability may play a fertilizing role, while the concurrent pH drop may exert pressure on microalgal cells, especially during the night period. It is known that elevated CO2 concentrations downregulate CO2-concentrating mechanisms (CCMs), and intracellular concentrations of dissolved inorganic carbon in diatoms grown under elevated CO2 levels can be much lower than that in low CO2-grown ones. Such a reduced CO2 availability within cells in response to increased CO2 in the water can lead to enhanced photorespiration due to an increased O2 to CO2 ratio around the carboxylating and oxygenating enzyme, RuBisCO. Therefore, negative and positive effects of OA may depend on light levels, since the saved energy due to downregulation of CCMs can benefit growth under light-limited conditions but enhance photoinhibition under light-excessive conditions. OA affects metabolic pathways in phytoplankton. It augments Β-oxidation and the citric acid cycle, which accumulates toxic phenolic compounds. In the upper mixed layer, phytoplankton are exposed to excessive PAR and UV radiation (UVR). The calcareous incrustations of calcified microalgae, known to shield the organisms from UVR, are thinned due to OA, exposing the cells to increased solar UV and further inhibiting their calcification and photosynthesis, reflecting a compounded impact. Such UV and OA interactive effects are expected to reduce primary productivity in oligotrophic pelagic surface waters. In this chapter, we review and analyze recent results on effects of OA and UV and their combined effects on marine photosynthesis of microalgae, which falls in the context of marine photosynthesis under changing ocean environments and multiple stressors.
CRIS-Team Scopus Importer:2024-12-16
Keywords: CO; Marine photosynthesis; Ocean acidification; Phytoplankton; Solar UV radiation